2013
DOI: 10.2306/scienceasia1513-1874.2013.39.174
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of intron 22 and intron 1 inversions of the factor 8 gene using an inverse shifting PCR method in severe haemophilia A patients

Abstract: Haemophilia A (HA) is an X-linked recessive bleeding disorder caused by several mutations in the F8 gene, whose inversion causes most of the mutation in 40% of severe HA patients. Methods such as long distance PCR and southern blot have been exploited to analyse intron 22 inversion in the F8 gene. For this purpose, we used an inverse shifting PCR assay, a novel genetic diagnostic method, for the detection of intron 22 inversion in severe HA patients. A screen for the presence of intron 22 and intron 1 inversio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 30 publications
3
3
0
Order By: Relevance
“…Rossetti et al observed the presence of inv22 in 45%‐50% of severe patients 9 . Moreover, in similar reports in Spain, Italy, Argentina, India, Egypt, Mexico, and Iran, inv22 is interpreted as the most frequent cause of severe HA 20‐22 . It should be noted that we reported the highest prevalence of inv22 mutation (40%), and this strongly supports previous studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Rossetti et al observed the presence of inv22 in 45%‐50% of severe patients 9 . Moreover, in similar reports in Spain, Italy, Argentina, India, Egypt, Mexico, and Iran, inv22 is interpreted as the most frequent cause of severe HA 20‐22 . It should be noted that we reported the highest prevalence of inv22 mutation (40%), and this strongly supports previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…9 Moreover, in similar reports in Spain, Italy, Argentina, India, Egypt, Mexico, and Iran, inv22 is interpreted as the most frequent cause of severe HA. [20][21][22] It should be noted that we reported the highest prevalence of inv22 mutation (40%), and this strongly supports previous studies. In most reports, the frequency of inv1 mutation has been stated to be 0%-5% of patients with severe HA.…”
Section: Discussionsupporting
confidence: 90%
“…Our findings confirm those of previous studies. The frequency of Inv 22 in our study was 44 %, which is similar to that in populations studied in the United Kingdom [13], Spain [17], Italy [18], Argentina [19,20], India [21], Egypt [22], Iran [23], Mexico [24], Hungary [15], and Costa Rica [25]. On the basis of these results, we concluded that the incidence in different populations is similar.…”
Section: Discussionsupporting
confidence: 86%
“…Our study showed that 1 (2 %) of 50 patients carried Inv 1. [6] in the United Kingdom, 0 % in Hungary [15], 0 % in Mexico [24], 0 % in Costa Rica [25], and 7 % in Iran [23].…”
Section: Discussionmentioning
confidence: 99%
“…This positive frequency is similar to previous studies from Egypt (46.1%), Iran (47%), and Iraq (36.3%) but lower than Jordan (52%) and Saudi Arabia (50%). It is higher than Albania (10.5%), Tunis (22.7%), Lebanon (29%), and the United Kingdom (17.6%) [13][14][15][16][17][18]. We detected inhibitors in 7.1% of Inv22 positive patients during our research.…”
Section: Discussionmentioning
confidence: 52%